Spirulina in diets of Japanese quail: Productive performance, digestibility, and egg quality - Maria Cristina de Oliveira; Matheus Andrade Dias Oliveira; Nathália Rodrigues Gonçalves; Pauliny do Carmo Ferreira; Diego Silva Lima; Ulcimar Martins Arantes (Acta Scientiarum: Animal Sciences, 2023)
The present study evaluated the effects of dietary inclusion of spirulina on productive performance, nutrient utilization, and egg quality of Japanese quails. One hundred twenty quails were included in a completely randomized design with four treatments and five replicates. Treatments consisted of a control diet and three diets containing 0.3, 0.6, or 0.9% of spirulina powder. Spirulina inclusion had no effect (p > 0.05) on the productive performance, digestibility coefficients of dry matter and ether extract, calcium and phosphorus retention, weight and pH of the eggs, yolk index, albumen quality, and eggshell thickness when compared with the control diet. However, crude protein consumption was higher (p < 0.05) and the digestibility coefficient of crude protein was lower (p < 0.05) in birds in the 0.9% and 0.3% spirulina inclusion groups, respectively. The weights of the yolk and eggshell were improved (p < 0.007) by the inclusion of 0.6% and 0.9% and 0.9% spirulina, respectively. Quails fed diets containing 0.3% and 0.6% spirulina exhibited lower specific gravity of eggs (p < 0.019) than those fed diets containing 0.9% spirulina. Therefore, spirulina inclusion at 0.9% improved the eggshell quality and reduced the total lipid levels in the yolks.